PENGARUH EVA, EARNINGS DAN ARUS KAS OPERASI TERHADAP STOCK RETURN - Elfina Astrella Sambuaga (Jurnal Akuntansi Bisnis, 2017)
This study analyzed the influence of economic value added, residual income, and two mandated performance measures, earnings and cash flow from operations to the shareholders’ return of mining’s companies that listed on Indonesian Stock Exchange. This study was also intended to know which performance measures have the most significant effect to the stockholders’ returns. This study used linier regression to see the contribution from each independent variables influenced stockholders’ return. The hypotheses was economic value added, earning and cash flow operation have significant influence  to the stockholder’ return. The most significant effect was from cash flow operation regression. The next variable which has significant effect also were EVA and earning. Keywords: EVA, earning, cash flow from operations, stock return